Chapter La «gita di Fiandra»: globi, libri e carte geografiche per Ferdinando II de' Medici nella corrispondenza diplomatica di Giovan Battista Gondi - Brovadan, Carlotta Paola (Studi e saggi, 2020)
In the summer of 1634 the grand-ducal ambassador resident in France Giovan Battista Gondi made an undercover journey to Spanish Netherlands to meet Maria de' Medici and tried to persuade her to leave the Habsburg territories for Florence. Despite the failure of the negotiations, a series of unpublished letters exchanged between Gondi and the first secretary of the Grand Duchy Andrea Cioli will serve as an opportunity to analyze which cultural and artistic affairs involved the Tuscan agent alongside the political events he primarily dealt with. In his letters Gondi described different artefacts that could have been acquired for the Medici collection, and publications that could have contributed to the reputation of the Grand Duke or, on the contrary, jeopardized it.